Grounded research: a modified grounded theory for the business setting - Whiteley, Alma (Association of Qualitative Research (RMIT Publishing), 2004)
Two concepts are presented for discussion in this paper, grounded research and socially stable constructs. The methodology used to investigate change on the waterfront in Western Australia was instrumental in formulating these two ideas. The paper starts with a review of the methodological thinking which led to and developed from the fieldwork. The theoretical perspectives of phenomenology and symbolic interactionism were adopted and it was intended to implement the principles of grounded theory (Glaser & Strauss, 1965, 1967) in the research design. Institutionalised structures and functions within the organisation and trade unions meant that another framework was imposed for us to work within and achieving the degree of emergence required for grounded theory became difficult within this business setting. During the qualitative analysis respondents talked about some personal constructs (such as trust and communication) as if they were factually present. To add strength to the constructs, and after they were judged to be ‘socially stable’, they were treated as ‘quasi facts’ and used as items on a questionnaire. Such activities undermined the principles of grounded theory, and yet, we believe, we did remain grounded. We coined the term grounded research to acknowledge the grounded theory method whilst signaling its problematic nature for some types of business research.